La “psiche estesa” tra Kant e Freud - Carignani, Paolo (Con-Textos Kantianos. International Journal of Philosophy, 2021)
This paper is inspired by one of Freud’s last notes, which is famous for its astonishing conclusion: “Psyche is extended; knows nothing about it,” which describes the perception of space as a product of the extension of the psychic apparatus, and compares it with Kant’s a priori categories. The Author reconstructs the historical background of this idea as part of a long discussion between Freud and his pupil Marie Bonaparte in the second half of 1938, and shows how the relationship between body and psychic functions in Freud’s thought was influenced by his intellectual debt to Kant. Through an outline of the influence of Kantian philosophy on the emerging Naturphilosophie in fin de siècle Vienna, the Author aims to show the profound influence of Kantian philosophy on the development of Freud’s thought. By committing to a modern and non-dualistic conception of the relationship between body and mind, Freud conceives an indissoluble bond between the mind and, not only the brain, but the whole body and its spatial extension. The Author concludes by identifying a close link between the aphorism of 1938 and Kantian pre-Critique thought, and, more generally, highlighting the influence of the Königsberg philosopher on the relationship between mind and body and on the perception of time and space in Freudian thought.